La villégiature anglaise et l’invention de la Côte d’Azur - Alain Bottaro (In Situ)
In many respects, the French Riviera is an English invention. First, it is an invention in the etymological sense of the term. Between 1760 and 1860, the coast of eastern Provence and of the region of Nice (like other areas outside Europe) was “discovered” by foreign travelers on the Grand Tour who gazed at the unsullied nature of the Mediterranean and perceived it as another Garden of Eden. Then such first-hand observations were appropriated by others through literary or iconographic representations such as travelogues or vedute. Finally came « launch time », as the expression goes: that is, the progressive inclusion of local towns in the ranks of top resorts for international travelers. It is indeed above all a British invention: from the second half of the 18th century to the 20th century, travelers from the British Isles were the creators, the propagators, and the main protagonists of the Riviera as a touristic haven. The early stages of the British presence from Cannes to Menton between 1760 and 1860 offer an exceptional field of study with regard to the process of touristic invention, not only because of its precocity and its duration but also to the diversity of its manifestations and its consequences. The coast between the Esterel massif and the first foothills of the Apennines stands out and is identified in the minds of the first travelers as the gateway to Italy. Until the mid-19th century, the Riviera remains linked in the imagination to the Grand Tour or the voyage to Italy. The beginnings of the habitual winterstay in Nice are evident, however, as early as the 1760’s. Thus, neighborhoods of English holiday homes start to grow early on and fashion the landscape through the introduction of new building methods and new town planning. The first few colonies of winter visitors were the New Borough in the Croix de Marbre section of Nice, the Croix des Gardes district in Cannes, or Carnolès or Garavan in Menton. Built up on the edge of town and on the fringe of local society, these colonies exercise increasing influence on the locals because of the financial capital they can wield and the fame of their most illustrious members. Among these personalities, Lord Brougham in Cannes and James Henry Bennett in Menton are notable as the creators of the new resorts between 1834 and 1860. The British seasonal communities led to cultural and technical transfers whose numerous manifestations profoundly changed the local economy and, as a result, traditional local society. The way of life of the winter visitors and their perception of Mediterranean landscapes gave rise between 1780 and 1860 to original projects for seaside villas, gardens, and communities. The introduction of seabathing on the Riviera before 1860 is emblematic of these British cultural transfers. The originality of Nice lies in the double influence of Italian and British models which are interwoven in local bathing practices and architecture.